The Child AbuThe Child Abuse Issue “Do Aggregate Income, Primary Trained Teachers and Unemployment Matter?”se Issue “Do Aggregate Income, Primary Trained Teachers and Unemployment Matter?” - Rambeli, Norimah; Hashim, Asmawi; Zakariya, Zainizam; Hashim, Emilda; Othman, Mohamad Khairi Haji; Utami, Sri (International Journal of Psychosocial Rehabilitation, 2020)
The main purpose of this study is to examine the linkages of independent variable including aggregate income, consumer price index, women labour force, unemployment, primary train teachers on child abuse rates in Malaysia. In term to examine the impotency of each independent variable on child abuse case, this study has applied the Ordinary Least Squares (OLS) approach to derive the estimation model. The findings suggest that there are three independant variables that give a positive impact to child abuses rate, woman labor force, consumer price index and aggregate income. In addition, the findings suggest that the woman labour force (t* = 3.927977), Consumer price Index (t* = 2.622482), and aggregate income (t* = 2.399656) significant in influencing the child abuse case in the long term for Malaysia. Further, under t-test procedure for estimated model, the study has proved that the woman labour force is the most significant variable contributes for child abuse incident. In implication, child abuse incident is a positively related to woman labour force, consumer price index and aggregate income in Malaysia. In other words, the government should implement policies specifically aimed at working women to address the increasing issue of child abuse in Malaysia. The female worker should be granted less time working hour or providing a childcare center near the workplace. This way, working women will be able to spend more time with their children. For example, for government employees, each department should provide its own childcare center.